An optimal nonlinear fractional order controller for passive/active base isolation building equipped with friction-tuned mass dampers - Akbari, Morteza; Zamani, Abbas-Ali; Seifi, Mohammad; Pantò, Bartolomeo; Falborski, Tomasz; Jankowski, Robert (Communications in nonlinear science & numerical simulation, 2025)
•The combination of active base isolation with friction-tuned mass dampers enhances the seismic performance of the structure.•Remarkable reduction in the peak displacement, acceleration, and inter-storey drift of a building during earthquakes using the NFOC controller.•Optimizing parameters enhances system performance.•The FTMD system has underperformed due to the high sensitivity of friction force compared to other systems. This paper presents an optimal nonlinear fractional-order controller (ONFOC) designed to reduce the seismic responses of tall buildings equipped with a base-isolation (BI) system and friction-tuned mass dampers (FTMDs). The parameters for the BI and FTMD systems, as well as their combinations (BI-FTMD and active BI-FTMD or ABI-FTMD), were optimized separately using a multi-objective quantum-inspired seagull optimization algorithm (MOQSOA). The seismic performances of the BI, FTMD, BI-FTMD, and ABI-FTMD systems for a 15-storey building subjected to two far-field (Loma Prieta and Landers) and two near-fields (Tabas and Northridge) earthquakes were evaluated. The results indicated that structures with BI, FTMD, BI-FTMD, and ABI-FTMD systems outperformed the uncontrolled structure in reducing structural responses during the design earthquakes (Loma Prieta and Tabas). However, under validation earthquakes (Landers and Northridge), the peak acceleration of the building with the FTMD system was worse than that of the uncontrolled structure during the near-field Northridge earthquake. To address this issue, we proposed a combination of the active BI system and the FTMD system. Time history analysis results demonstrated that for the building equipped with the ABI-FTMD system, the peak displacement, peak acceleration, and peak inter-storey drift were reduced by approximately 60%, 64%, and 78%, respectively, as compared to the uncontrolled structure.